The end of silence - Marching, Soe Tjen, author. Link Link
1 online resource.
Keywords: In the late 1960s, between one and two million people were killed by Indonesian president Suharto's army in the name of suppressing communism-and more than fifty years later, the issue of stigmatisation is still relevant for many victims of the violence and their families. The End of Silence presents the stories of these individuals, revealing how many survivors from the period have been so strongly affected by the strategy used by Suharto and his Western allies that these survivors, still afraid to speak out, essentially serve to maintain the very ideology that led to their persecution.